Anti-Dumping Policies and Safeguard Measures in the Context of Costa Rica’s Economic Liberalization - Monge-González, Ricardo; Monge-Ariño, Francisco (World Bank, Washington, DC, 2012)
This paper reviews the most important changes, both in the economy and in the legal and institutional framework, to deal with unfair trade practices that Costa Rica has experienced during its trade liberalization process. It also evaluates whether the sectors that as a result of such a process have been facing increased foreign competition, and may have attempted to use the World Trade Organization (WTO) rules adopted by Costa Rica as a protectionist instrument. Costa Rica's legal framework against unfair trade practices at the multilateral level emerged when the country adopted the WTO rules on antidumping policies and safeguard measures. That has been reinforced at the bilateral level through the subscription of free trade agreements with Central America, Mexico, the Dominican Republic, Chile, and Canada. So far, only six antidumping petitions and five safeguards have been received by the government. In reviewing these petitions, the government has paid particular attention to the impact of any action on the competitiveness of the domestic market and on the possibility that it would support modernization of the industry. Behind the political acceptance of this disciplined approach lies widespread recognition of the social as well as economic progress that liberalization has supported.